2013
DOI: 10.1179/1743132813y.0000000258
|View full text |Cite
|
Sign up to set email alerts
|

Lathyrism: has the scenario changed in 2013?

Abstract: Lathyrism is now rarely seen as a clinical disease in general, medical or neurology outpatient departments, throughout the world. Eating patterns of seeds of Lathyrus sativus are still prevalent focal points in parts of the world. Question arises, why are we not seeing cases of lathyrism? Is it that the disease has changed its profile, with the changing socioeconomic status of the poor or underdeveloped or moderately developed countries? Is it that the seeds of lathyrus are less toxic now? Is it that the body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…24 Cyanide detoxification is mediated by the enzyme rhodanese, which requires sulfur (provided by sulfur-containing amino acids) and is responsible for the conversion of cyanide into thiocyanate, which is excreted in the urine. 26 Similar to konzo, outbreaks of neurolathyrism typically occur during times of drought, flooding, or wars, with the rural poor being most vulnerable. The World Health Organization recommends a varied diet and immediate multivitamin therapy to prevent or treat other potential complications related to vitamin deficiencies.…”
Section: Konzomentioning
confidence: 99%
“…24 Cyanide detoxification is mediated by the enzyme rhodanese, which requires sulfur (provided by sulfur-containing amino acids) and is responsible for the conversion of cyanide into thiocyanate, which is excreted in the urine. 26 Similar to konzo, outbreaks of neurolathyrism typically occur during times of drought, flooding, or wars, with the rural poor being most vulnerable. The World Health Organization recommends a varied diet and immediate multivitamin therapy to prevent or treat other potential complications related to vitamin deficiencies.…”
Section: Konzomentioning
confidence: 99%
“…[1] A causal relationship between the excessive consumption of L. sativus and neurolathyrism (an upper motor neuron disorder characterized by a spastic paraparesis of the lower limbs) is well known for several decades. [2] It has been discussed that neurolathyrism has been only reported in the extreme conditions of drought or famine [3] but not in normal conditions and afflicts predominantly the lower socioeconomic class. The last recorded episode of the disease was from Ethiopia during the 1995-1997 famine, and in India, it has virtually disappeared during the past three decades despite the continued cultivation and consumption in several states.…”
Section: Introductionmentioning
confidence: 99%
“…Reference had been made by Hippocrates and Galen to the impotentia crurum of those who fed on what was called ervum, ..." (Buchanan, 1904). While lathyrism epidemics occurred during droughts in France, Germany, Spain, India, and Algeria from early nineteenth century to early twentieth century, and in Bangladesh (Haque et al, 1994), Afghanistan (Arya et al, 1988), India (Khandare et al, 2014;Mishra et al, 2014), Nepal (Hamilton, 1978), and Ethiopia (Fikre et al, 2011) from the late twentieth century to early twenty-first century, the most systematic studies were carried out in India during the Colonial rule from 1833 to 1920. It was shown that lathyrism epidemics occurred during droughts when the population depended on Lathyrus sativus (grasspea), a drought resistant crop, for supply of calories (Buchanan, 1904).…”
Section: Introductionmentioning
confidence: 99%